ANALISIS USABILITY PADA WEBSITE SERVIO MENGGUNAKAN METODE THINK ALOUD - Triono, Andri Maruli Imanuel; Musdar, Izmy Alwiah; Surasa, Hendra (STMIK KHARISMA Makassar, 2025)
Service Electronica Online (SERVIO) is a web-based application project developed to provide online repair services for electronic goods. SERVIO can be accessed online through the website (https://serviceonline.bopolewali.com). The usability of the SERVIO website requires a usability analysis with the aim of ensuring that the website is accepted and used by users, as well as identifying the shortcomings of the SERVIO website. Usability testing on the SERVIO website will be conducted using the Think Aloud method. Based on the results of the usability test of the SERVIO website, respondents believe that the flow of the website is still not understandable. After the errors found in the website display were identified, recommendations were provided in the form of design improvements. The changes in design can be found in the login menu, navigation, service messages, and service progress.